PELAKSANAAN KEWENANGAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG TERHADAP PRESERVASI JALAN BERDASARKAN PERATURAN WALIKOTA PEKANBARU NOMOR 94 TAHUN 2016 TENTANG KEDUDUKAN, SUSUNAN ORGANISASI, TUGAS DAN FUNGSI SERTA TATA KERJA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU - Wiraya Aidiliya Utama; Zulfikar Jayakusuma; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Article 19 Paragraph (2) of Pekanbaru Mayor Regulation Number 94 of 2016 states that thetask of the road and bridge preservation section is to preserve roads and bridges in order tomaintain steady road conditions in accordance with the level of service and ability when theroad is built and operated. However, it is still not applied, especially on roads in PekanbaruCity which is the authority of the Pekanbaru Public Works and Spatial Planning Office incarrying out road preservationThis type of research is sociological legal research, because it is based on field research,namely by collecting data from interviews, questionnaires, and literature reviews that have arelationship with the problem to be studied assisted by primary, secondary and tertiary dataThis research was conducted in the Regional People's Representative Council of PekanbaruCity, Public Works and Spatial Planning Office of Pekanbaru City, while the population andsample are all parties related to the problem studied. This study used qualitative data analysisand produced descriptive data.It can be concluded that, First, the Implementation of the Authority of the Public Works andSpatial Planning Office of Pekanbaru City on Road Preservation Based on Pekanbaru MayorRegulation number 94 of 2016 has not performed its duties well in the road preservationprogram Second, the inhibiting factors for the implementation of the authority of thePekanbaru City Public Works and Spatial Planning Office on Road Preservation based onPekanbaru Mayor Regulation number 94 of 2016 are poor drainage factors, weather factors,WWTP (Wastewater Management Plant) project factors, human resource factors and budgetfactors. Third, efforts made to overcome inhibiting factors are to preserve roads in PekanbaruCity regularly, improve drainage on damaged roads, and supervise the implementation of themayor's regulation.Keywords: Authority-Mayor Regulation-Road Preservation